Genetic polymorphism analysis of MICB gene in Jing ethnic minority of Southern China. (22nd August 2018) - Liu, Xuexiang; Chen, Xiang; Wei, Xiaomou; Meng, Yuming; Liu, Limin; Dai, Shengming
Abstract : In the present study, the polymorphism in the 5′‐upstream regulation region (5′‐URR), coding region (exons 2‐4), and the 3′‐untranslated region (3′‐UTR) of MICB gene were investigated for 150 healthy unrelated Jing individuals in Guangxi Zhuang Autonomous Region, by using PCR‐SBT method. A total of 14 variation sites in the 5′‐URR, 9 in coding region, and 6 in the 3′‐UTR were detected in the Jing population. The MICB gene seems to present two different lineages showing functional variations mainly in nucleotides of the promoter region. Nineteen different MICB extended haplotypes (EHs) encompassing the 5′‐URR, exons 2‐4, and 3′‐UTR were found in this population, and the most frequent was EH2 (20.33%). The findings here are of importance for future studies on the potential role of regulation region of MICB gene in disease association, transplantation, viral infection, and tumor progression among Jing population.